end
def test_description
+ note = create(:note)
+ assert_equal "Default note's description", note.description
+
+ note = create(:note, :description => "Test description #1")
+ assert_equal "Test description #1", note.description
+
comment = create(:note_comment)
- assert_equal comment.body, comment.note.description
+ assert_equal "Default note's description", comment.note.description
- user = create(:user)
- comment = create(:note_comment, :author => user)
- assert_equal comment.body, comment.note.description
+ comment = create(:note_comment, :note => build(:note, :description => "Test description #2"))
+ assert_equal "Test description #2", comment.note.description
end
def test_author
+ user = create(:user)
+
+ note = create(:note, :author => user)
+ assert_equal user, note.author
+
comment = create(:note_comment)
assert_nil comment.note.author
- user = create(:user)
- comment = create(:note_comment, :author => user)
+ comment = create(:note_comment, :author => user, :note => build(:note, :author => user))
assert_equal user, comment.note.author
end